Magnesium Hydride-Mediated Sustainable Hydrogen Supply Prolongs the Vase Life of Cut Carnation Flowers via Hydrogen Sulfide - Li, Longna; Liu, Yuhao; Wang, Shu; Zou, Jianxin; Ding, Wenjiang; Shen, Wenbiao (Frontiers in Plant Science, 2020)
Magnesium hydride (MgH2) is a promising solid state hydrogen source with high storage capacity (7.6 wt%). Although it is recently established that MgH2 has potential application in medicine since it sustainably supplies hydrogen gas (H2), the biological functions of MgH2 in plants have not been observed yet. Also, the slow reaction kinetics restricts its practical applications. In this report, MgH2 (98% purity; 0.5-25 μm size) was firstly used as hydrogen generation source for postharvest preservation of flowers. Compared to the direct hydrolysis of MgH2 in water, the efficiency of hydrogen production from MgH2 hydrolysis could be greatly improved when citrate buffer solution (CBS) is introduced. These results were further confirmed in flower vase experiment by showing higher efficiency in increasing the production and the residence time of H2 in solution, compared to hydrogen-rich water (HRW). Mimicking the response of HRW and sodium hydrosulfide (NaHS; a hydrogen sulfide donor), subsequent experiments discovered that MgH2-CBS not only stimulated hydrogen sulfide (H2S) synthesis, but also significantly prolonged the vase life of cut carnation flowers. Meanwhile, redox homeostasis was reestablished, and the increased transcripts of representative senescence-associated genes, including DcbGal and DcGST1, were partly abolished. By contrast, above responses were obviously blocked by the inhibition of endogenous H2S with hypotaurine (HT), a H2S scavenger. These results clearly revealed that MgH2-suppling H2 could prolong the vase life of cut carnation flowers via H2S signaling, and our results therefore open a new window for the possible application of hydrogen-releasing materials in agriculture.